Analisis Strategi Kepala Sekolah dan Guru dalam Membentuk Karakter Siswa - Eliyanto .; Moh. Oky Sadam Basri (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research is motivated by the existence of a phenomenon where there are schools with adequate facilities and infrastructure, have a third floor building that is used specifically to accommodate students but in fact the expectations are that the third floor building can accommodate 500 students but is only used by less than 20 students, and this phenomenon occurred at SMK Ma'arif 2 Gombong. Meanwhile, SMK Ma'arif 5 Gombong has limited facilities and infrastructure and can only accommodate a limited number of students, where the distance between the two schools is close but has 100 students at SMK Ma'arif 5 Gombong. This research uses a type of qualitative research with a phenomenological approach to the delivery of education at SMK Ma'arif 5 Gombong. The researcher as the main instrument, with data collection techniques through observation, interviews, and documentation studies. All data was analyzed using an interactive model with the flow: data recording, data reduction, data presentation, and conclusions. The results of this study can be concluded that: First, in strategic planning the principal of SMK Ma'arif 5 Gombong is more dominant due to situational reasons at the time he first served as principal and the personal experience of the principal of SMK Ma'arif 5 Gombong. Second, in implementing the strategy, SMK Ma'arif 5 Gombong can implement the strategy well where it is reflected in the atmosphere of the school environment, the character of teachers and students as well as the climate and culture that is built at SMK Ma'arif 5 Gombong. Third, strategy evaluation is carried out periodically either once a month or once a year, besides that evaluation is carried out directly by the school principal or indirectly with the assistance of the school development team. The results of the evaluation will be taken into consideration in making improvements to the strategy or stating if the strategy applied is appropriate.